2021
DOI: 10.1177/09544062211020344
|View full text |Cite
|
Sign up to set email alerts
|

Design and remote collaboration control of asymmetric rigid-flexible hybrid-driven lower limb rehabilitation robot

Abstract: A double-end lower limb rehabilitation robot is introduced in the paper, which can realize the rehabilitation training of the abduction and abduction, internal rotation and external rotation of human lower limb. The kinematics and dynamics of the robot are analyzed. Based on the motion trajectory planning of the lower limb rehabilitation robot, the motion state and dynamic state of the cable are analyzed. In order to realize the good remote cooperative control between the rehabilitation physician terminal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As can be seen from Figure 11, the motion trend of doctor-side and patient-side is similar, both are in the workspace. In addition, it is also observed that the maximum tracking error between doctor-side and patient-side is 45.09 mm, which is smaller than that proposed by Wang et al 22 The tracking error is caused by the asymmetry of the bilateral structure and the difference of the human leg model, and the force and motion are transmitted using cable. Taking all the above factors into account, this shows that the bilateral system based on the IPDAM can meet the requirements of rehabilitation training and complete the rehabilitation task well, which has guiding significance and important value for the application of bilateral control strategy in lower limb rehabilitation robots.…”
Section: Experimental Studymentioning
confidence: 61%
See 2 more Smart Citations
“…As can be seen from Figure 11, the motion trend of doctor-side and patient-side is similar, both are in the workspace. In addition, it is also observed that the maximum tracking error between doctor-side and patient-side is 45.09 mm, which is smaller than that proposed by Wang et al 22 The tracking error is caused by the asymmetry of the bilateral structure and the difference of the human leg model, and the force and motion are transmitted using cable. Taking all the above factors into account, this shows that the bilateral system based on the IPDAM can meet the requirements of rehabilitation training and complete the rehabilitation task well, which has guiding significance and important value for the application of bilateral control strategy in lower limb rehabilitation robots.…”
Section: Experimental Studymentioning
confidence: 61%
“…Although the performance of IPDAM will change with the increase of n , the position tracking performance and tracking error will be reflected: in the case of the patient-side’s free movement, the tracking error of the IPDAM is reduced by about 5 mm compared with the unilateral PD method; in the case of non-free movement, the error of the IPDAM becomes worse, which increases about 6 mm compared with the unilateral PD method. Compared with the control strategy proposed by Wang et al, 22 its mean error of the motion trajectory of the end-effector is 54.37 mm, the maximum error of the IPDAM( n = 6) is 47.82 mm. Obviously, the position tracking performance of IPDAM is slightly better than above Wang et al proposed (Figure 9).…”
Section: Experimental Studymentioning
confidence: 82%
See 1 more Smart Citation
“…Since the sum of squares of elements (1,4), (2,4), and (3,4) in equations ( 6), (7), and ( 8) are equal, it is obtained that:…”
Section: Kinematic Inverse Solutionmentioning
confidence: 99%
“…As a new type of rehabilitation equipment, the exoskeleton rehabilitation robot could help patients with impaired extremity movement function to achieve rehabilitation training, thus reducing the labor intensity of health care workers and solving the problem of social medical resource tension. 1,2 However, the main purpose of rehabilitation training is to improve the movement range and muscle strength of the affected extremity for patients. If patients are unable to achieve the training requirements with rehabilitation robots, they miss the optimal treatment period for rehabilitation training, which affects the recovery of patients’ motor ability and reduces patients’ recognition of robot-assisted rehabilitation training.…”
Section: Introductionmentioning
confidence: 99%